Medical students’ personal experiences, religion, and spirituality explain their (dis)comfort with a patient’s religious needs (Canadian Medical Education Journal, 2020)
Background: Physicians often avoid discussing patients’ religious and spiritual concerns, even though most patients (i.e., 50-94%) want integrated care.  To address this gap, medical students interviewed a Standardized Patient (SP) who was upset because the daughter did not confront her fiancée about converting to Orthodox Judaism.  Students reflected on how their own religion and spirituality affected engaging with their patient.Methods: With a 97% response rate, 231 first-year medical students responded to open-ended questions about their patient encounter.  For this quantitative content analysis, we used inductive reasoning, identifying three themes:  (1) impact of students’ own religion on their comfort, (2) change in comfort, and (3) their learning. We used deductive reasoning to compare qualitative results from half of the students who began the curriculum with a questionnaire about their own spirituality with the other students completing afterwards.Results: Most students said being religious positively influenced their comfort, whether they were also Orthodox Jewish or from a different religion. Among uncomfortable students (6.5%), some attributed this to not being religious. Some students (4.8%) grew more comfortable discussing the religious issue, and 18.2% became uncomfortable due to lacking knowledge of Orthodox Judaism and the awkwardness of the topic.  Students who had completed the questionnaire beforehand gave more comments about connecting with their patients than students who completed the questionnaire afterwards (X2=11.047, p